2016
DOI: 10.1016/j.celrep.2015.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Platinum and PARP Inhibitor Resistance Due to Overexpression of MicroRNA-622 in BRCA1-Mutant Ovarian Cancer

Abstract: High-grade serous ovarian carcinomas (HGSOCs) with BRCA1/2 mutations exhibit improved outcome and sensitivity to double-strand DNA break (DSB)-inducing agents [i.e. platinum and Poly(ADP-ribose) polymerase inhibitors (PARPis)] due to an underlying defect in homologous recombination (HR). However, resistance to platinum and PARPis represents a significant barrier to the long-term survival of these patients. Although, BRCA1/2-reversion mutations are a clinically validated resistance mechanism, they account for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 32 publications
4
94
0
Order By: Relevance
“…A recent example is the regulation of miR-622, which promotes PARPi resistance by modulating the balance of DNA repair pathways [65]. MiR-622 selectively inhibits the expression of NHEJ components (Ku70/80), which promotes genome stabilization following the exposure to DNA damaging agents or PARPi.…”
Section: Parp Inhibitor Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…A recent example is the regulation of miR-622, which promotes PARPi resistance by modulating the balance of DNA repair pathways [65]. MiR-622 selectively inhibits the expression of NHEJ components (Ku70/80), which promotes genome stabilization following the exposure to DNA damaging agents or PARPi.…”
Section: Parp Inhibitor Resistancementioning
confidence: 99%
“…MiR-622 selectively inhibits the expression of NHEJ components (Ku70/80), which promotes genome stabilization following the exposure to DNA damaging agents or PARPi. Upon examination of miR-622 expression in BRCA-inactivated ovarian cancer, high expression of miR-622 predicted a worse disease free survival (14.7 versus 19.8 months; log rank p = 0.03) and overall survival (39 versus 49.3 months; log rank p = 0.03) [65]. Another miRNA (miRNA-182) was also observed to increase PARPi sensitivity via downregulation of BRCA1 [66].…”
Section: Parp Inhibitor Resistancementioning
confidence: 99%
“…Similar to studies in breast cancer, high expression of miR-622 in EOC was associated with loss of ku protein from the homologous recombination pathway and poor outcome. This suggests that miR-622 was associated with resistance to chemotherapy including poly ADP ribose polymerase (PARP) inhibitors (60). Since PARP inhibitors are now FDA approved for ovarian cancer therapy (61), this microRNA marker may be an additional marker useful for selecting appropriate candidates for this particular therapy.…”
Section: Microrna Molecules As Clinical Biomarkers For Eocmentioning
confidence: 99%
“…We have been systematically studying the role of microRNAs (miRNAs) in HRR and their role in mediating PARPi sensitivity (Choi et al, 2014, 2016; Moskwa et al, 2011). In this regard, using a candidate-based approach, we have recently shown that overexpression of a miRNA, miR-622, induces resistance to PARPi and platinum-based drugs in BRCA1 mutant ovarian carcinomas (Choi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, using a candidate-based approach, we have recently shown that overexpression of a miRNA, miR-622, induces resistance to PARPi and platinum-based drugs in BRCA1 mutant ovarian carcinomas (Choi et al, 2016). We observed that miR-622 regulated the expression of the Ku complex and suppressed NHEJ, thereby rescuing the HRR deficiency of BRCA1 mutant ovarian carcinomas and induced resistance to PARPi and platinum-based drugs.…”
Section: Introductionmentioning
confidence: 99%